2021
DOI: 10.1051/0004-6361/202038624
|View full text |Cite
|
Sign up to set email alerts
|

Dust polarized emission observations of NGC 6334

Abstract: Context. Molecular filaments and hubs have received special attention recently thanks to new studies showing their key role in star formation. While the (column) density and velocity structures of both filaments and hubs have been carefully studied, their magnetic field (B-field) properties have yet to be characterized. Consequently, the role of B-fields in the formation and evolution of hub-filament systems is not well constrained. Aims. We aim to understand the role of the B-field and its interplay with turb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 133 publications
(148 reference statements)
1
50
0
Order By: Relevance
“…Recently, observations with the James Clerk Maxwell Telescope (JCMT) of polarized dust emission at 850 µm revealed a detailed field morphology of NGC6334I(N) at clump scales (14 resolution, Arzoumanian et al 2021). To compare with ours, we show a zoomed map of the JCMT data (see Figure 3, left panel), where the pinched morphology is seen over a broader region encompassing both NGC6334I(N) and NGC6334I sources (NGC6334I is not covered by the ALMA data presented here) and outlined by translucent red lines.…”
Section: Polarized Dust Continuum Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, observations with the James Clerk Maxwell Telescope (JCMT) of polarized dust emission at 850 µm revealed a detailed field morphology of NGC6334I(N) at clump scales (14 resolution, Arzoumanian et al 2021). To compare with ours, we show a zoomed map of the JCMT data (see Figure 3, left panel), where the pinched morphology is seen over a broader region encompassing both NGC6334I(N) and NGC6334I sources (NGC6334I is not covered by the ALMA data presented here) and outlined by translucent red lines.…”
Section: Polarized Dust Continuum Emissionmentioning
confidence: 99%
“…The brightest regions studied in the millimeter and sub-millimeter are NGC6334I and NGC6334I(N) (McCutcheon et al 2000;Hunter et al 2014Hunter et al , 2017Sadaghiani et al 2020), where both regions appear to harbor high mass star formation. Besides the large scale mapping of polarized dust emission done by Planck (Planck Collaboration XXXV et al 2016), the magnetic field in NGC6334I(N) has been mapped via polarized dust emission at angular resolutions from ∼ 4 (Li et al 2006), ∼ 20 Vaillancourt (2011, ∼ 14 (Arzoumanian et al 2021), and ∼ 2 (Zhang et al 2014;Li et al 2015) which found a field shape evolving from a clear pinch at the high density peaks at large scales to an "hourglass" shape at shorter scales. We follow the nomenclature used by Hull & Zhang (2019), where we refer to cloud scales to structures ∼ 10 pc, clump scales ∼ 1 pc, core scales between 0.1 to 0.01 pc, and envelope scales to structures ∼ 1000 au.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the BISTRO surveys have shown highly resolved magnetic fields and measurements of the field strengths in Orion A ), Oph-A (Kwon et al 2018), Oph-B (Soam et al 2018), Barnard 1 (Coudé et al 2019), Oph-C (Liu et al 2019), IC 5146 (Wang et al 2019), M16 (Pattle et al 2018), NGC 6334 (Arzoumanian et al 2021), and several other regions are under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade it has become clear that filaments play a critical role in assembling the material to form stars (e.g. Schneider & Elmegreen 1979;Bally et al 1987;Abergel et al 1994;Cambrésy 1999;Myers 2009;Hacar & Tafalla 2011;Peretto et al 2012;Hacar et al 2013;Palmeirim et al 2013;André et al 2014;Alves de Oliveira et al 2014;Peretto et al 2013;Könyves et al 2015;Marsh et al 2016;Hacar et al 2017;Ward-Thompson et al 2017;Williams et al 2018;Hacar et al 2018;Watkins et al 2019;Ladjelate et al 2020;Arzoumanian et al 2021). Even in clouds that are not apparently forming stars, or forming them very slowly (e.g.…”
Section: Introductionmentioning
confidence: 99%